Uji Kinerja Prototipe Mesin Skarifikasi Berbasis Motor Penggerak Untuk Benih Pare - Geraldo Adinugra Rimartin; Ais Nur Hasanah; Budi Wijayanto (JURNAL VIGOR, 2026)
Bitter gourd seeds (Momordica charantia L.) have a relatively hard seed coat that may restrict water absorption and delay germination, thus requiring an appropriate scarification treatment. Manual scarification using nail clippers is relatively effective; however, it is labor-intensive and time-consuming when applied to large quantities of seeds. This study aimed to analyze the performance of a prototype scarification machine driven by a transmission motor compared with manual scarification using nail clippers. The performance of the machine prototype was evaluated based on scarification effectiveness, working capacity, and time efficiency. In addition, germination tests were conducted on the scarified seeds. The performance test was carried out in four replications using 100 seeds per replication, while the germination test was conducted in four replications using 25 seeds per replication. The data were analyzed using a t-test at a 5% significance level. The machine prototype achieved an average scarification effectiveness of 38.50%, which was lower than that of the manual method at 87.75%. However, the prototype had ahigher working capacity of 20.79 seeds min?1 compared with 13.01 seeds min?1 for the manual method. The processing time required by the prototype was 4 min 51 s, which was shorter than the 7 min 43 s required by the manual method, resulting in a 37% improvement in processing-time efficiency. The germination test showed germination percentages of 65% for seeds treated using the machine prototype and 75% for seeds treated manually. The t-test indicated that the difference was not statistically significant, with a p-value of 0.176. Overall, the findings demonstrate that the motor-driven scarification machine prototype can increase working capacity and processing- time efficiency. Nevertheless, improvements to the hopper system, drive motor, and piercing-needle mechanism are required to enhance its scarification effectiveness.